Drug Target Investigation of N-p-Coumaroyl-N’-Caffeoylputrescine, a Naturally-Occurring Alkaloid Derived from Saxifraga tangutica - Chuang Liu; Jun Dang; Minchen Wu (Antioxidants)
The exploration of drug targets has always been a priority in new drug research, and this work is even more essential for natural active compounds. Saxifraga tangutica is a traditional Tibetan medicine with excellent antioxidant properties. In this study, an alkaloid, N-p-coumaroyl-N’-caffeoylputrescine (PCC), was first isolated from the plant, Saxifraga tangutica, with a DPPH scavenging rate of 0.936 μg/mL. To further identify its target, the drug affinity responsive target stability technique and multiple public databases were integrated to retrieve a total of 317 common targets from comprehensive screening. A further bioinformatics analysis not only identified 13 hub targets but also indicated PCC as having biological activities against cancer and affecting metabolic diseases. Integrating reverse virtual docking, molecular dynamics simulations, and cellular thermal shift assays ultimately focused on HSP90AA1 as the target of PCC. An in vitro study on liver (HepG2) cells and breast (MCF-7) cancer cells revealed that PCC modulates HSP90AA1, subsequently affecting Mut-p53 expression, triggering a cascade effect that reduced adriamycin-induced drug resistance in cells. Furthermore, a prediction of the absorption, distribution, metabolism, excretion, and toxicity was also applied to evaluate the drug-like properties of PCC. Overall, the integrated strategy used in this study successfully identified the target of PCC, providing a valuable paradigm for future research on the action targets of natural products.